Aquatic Hemiptera (Heteroptera) of Kazakhstan, with notes on life history, ecology and distribution - Esenbekova, Perizat Abdykairovna; Nurushev, Murat Zhusupbekovich; Homziak, Jurij (Zootaxa, 2015)
Based on extensive field collections (2000-2014) in Kazakhstan and a review of the material in the National Institute of Zoology of Kazakhstan, we identified 68 species of aquatic Hemiptera from 11 families. Most species have broad zoogeographic distribution, dominated by West Eurasian fauna (18 species) and West Palearctic fauna (10 species). Details of habitats, feeding types, and life history are included for the described species.